Temperature Dependence of the EPR Spectra of Gd0.5RE0.5 Ba2Cu3O7‐δ Compounds in the Orthorhombic and Tetragonal Phases - Guskos, N.; Triberis, G.P.; Lykodimos, V.; Windsch, W.; Metz, H.; Koufoudakis, A.; Mitros, C.; Gamari‐Seale, H.; Niarchos, D. (physica status solidi (b), 1991)
The materials Gd0.5RE0.5 Ba2Cu3O7‐δ (Re = Y, Sm, Eu, and La) are investigated in the orthorhombic (HTC) and tetragonal (non‐HTC) phases using EPR method. For both phases EPR signals associated with Gd ions are detected. In the tetragonal phase a strong temperature dependence of the intensities of this line is observed. These characteristics can be ascribed to the skin effect. A small polaron model is proposed to interpret the conduction mechanism of the tetragonal phase (semiconducting) of these samples. Copyright © 1991 WILEY‐VCH Verlag GmbH & Co. KGaA